Quantitative analysis of the rate of stride length and frequency using a device (Dittmann Sport) and the completion of the effectiveness of their relationship ran in 5000 for the general category of ages 21 years and older - faeq, Haider; matab, Suheir (Journal of Physical Education, 2012)
The research aims to study the quantitative analysis of the achievement in the effectiveness of the running in 5000, and also identify the average stride length and frequency using a device (Dittmann Sport) to hostile in 5000 to the category of applicants The sample of research (8) players from the squad of Iraq and the Police Club in athletics to the category of the public aged 21 years and older, was selected in the manner intentional, was carried out one test, a test of achievement of the effectiveness of running in 5000, with the application all specifications legal under international law to athletics to make race the effectiveness of the running in 5000, and after receiving the results of the analysis, the researcher extracted the statistical means it, and concluded as follows: There is no clear effect of the rate of stride length and frequency to deliver to the effectiveness of running (5000 m), as well as the quantitative analysis of the effectiveness of the speed run (5000 m) helps coaches to stand on their weaknesses when hostility. The researcher recommended the following: a quantitative analytical research of the various running events because of their significant role in assisting the completion of the development of coaches and players, as well as a qualitative analysis of the performance of the motor to run long-distance events.